Authorship order. Issue 2 (21st August 2018) - Helgesson, Gert; Eriksson, Stefan
Abstract : Considering the fact that authorship order plays such a significant role as a basis for scientific merit, this paper looks into the practices of authorship order from a research ethical perspective. We conclude that there is a wide variety of practices and no common understanding of what the different authorship positions signify. Authorship guidelines do not provide much help. We recognize that, regardless of what system for valuing authorship positions is used, it will be misleading and unfair in most applications because relative contributions vary in ways that are not captured by fixed value assignments to authorship positions. In theory, assigning percentage figures reflecting the relative contributions of the authors would solve that problem, but we argue that such a scheme is not likely to work in practice. It can also be questioned whether relative, rather than absolute, contributions should be the basis for scientific merit. Contributorship is discussed as an alternative, but is recognized to be insufficient both in communicating absolute and relative contributions, as standardly used. However, there may be a way forward with contributorship, but then, the level of detail needs to increase considerably and its application be standardized.